Low osmolality and shear stress during liposuction impair cell viability in autologous fat grafting. Issue 5 (May 2017) - Ismail, T.; Bürgin, J.; Todorov, A.; Osinga, R.; Menzi, N.; Largo, R.D.; Haug, M.; Martin, I.; Scherberich, A.; Schaefer, D.J.
Summary: Background: Liposuction and subsequent autologous fat grafting have become essential techniques for fat augmentation in plastic surgery. However, standard harvesting techniques that ensure the survival of adipocytes and stromal vascular fraction (SVF) cells and thus preserve the transplanted fat volume are lacking. In particular, the effect of different parameters of the tumescent solution has not been studied in this context. We hypothesized that the osmolality of the tumescent solution could have a significant effect on the survival of adipocytes and SVF cells. Methods: We developed two distinct in vitro models based on freshly harvested excision fat from patients undergoing surgical treatment. First, we investigated the effect of osmolality by incubating excision fat in different tumescent solutions and analyzed the total cell survival and the differentiation potential of SVF cells. Vital whole-mount staining, isolation yield of SVF cells, clonogenicity, and osteogenic and adipogenic differentiation capacities were analyzed. Second, we addressed the additional effect of mechanical stress by simulating a liposuction on pieces of excision fat after incubation with the tumescent solutions. Results: Osmolality of the tumescent solution by itself did not have a significant effect on adipocyte and SVF viability or SVF differentiation. However, when osmolality was combined with liposuction, a significant trend toward lower viability and more lipid droplets with lower osmolality was observed. Especially, SVF viability was significantly lower after liposuction with a hypotonic (150 mOsm/kg) solution. Conclusion: This study demonstrates the considerable effect of osmolality during liposuction and may lead to the development of "cell-protective" tumescent solutions.